2012
DOI: 10.4149/bll_2012_079
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of vitamin C in diazepam-induced apoptosis in rat thymocytes

Abstract: Diazepam, a peripheral-type benzodiazepine receptor ligand, is widely used as a therapeutic agent. On the other hand, peripheral-type benzodiazepines have been shown to induce apoptosis in different immune cell types. In this study, we examined the possible protective role of vitamin C in diazepam-induced apoptosis and evaluated the cellular content of glutathione during this process. Rat thymocytes were incubated for 24 hours with diazepam and increasing concentrations of vitamin C or with diazepam alone. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…There is a significant age-associated increase in apoptosis that affects the double-negative cell population of thymocytes, partly due to the elevated expression of the cell death gene caspase-3 in aged mice ( 35 , 36 ) . VC has been shown to inhibit thymocyte apoptosis by up-regulating the expression of the anti-apoptotic protein B-cell lymphoma-2 ( 37 39 ) . We found that the total number of thymocytes and the number of double-positive cells and CD4 + or CD8 + SP thymocyte subpopulations were markedly higher in the 0·2 % VC group than in the 0·02 % VC group after 1 year of dietary treatment, possibly reflecting the inhibitory effect of high-dose dietary VC intake on the apoptosis of thymocytes through the induction of B-cell lymphoma-2.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant age-associated increase in apoptosis that affects the double-negative cell population of thymocytes, partly due to the elevated expression of the cell death gene caspase-3 in aged mice ( 35 , 36 ) . VC has been shown to inhibit thymocyte apoptosis by up-regulating the expression of the anti-apoptotic protein B-cell lymphoma-2 ( 37 39 ) . We found that the total number of thymocytes and the number of double-positive cells and CD4 + or CD8 + SP thymocyte subpopulations were markedly higher in the 0·2 % VC group than in the 0·02 % VC group after 1 year of dietary treatment, possibly reflecting the inhibitory effect of high-dose dietary VC intake on the apoptosis of thymocytes through the induction of B-cell lymphoma-2.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the present study, Pavlovic et al (2012) evaluated the apoptotic power of BZDs on rat thymocytes, since they incubated cells for a twenty-four-hour period with a BZD. After this period, the authors found that exposure to the drug resulted in an increase in cell death by apoptosis.…”
Section: Discussionmentioning
confidence: 97%
“…a)Normal hepatocytes counteract apoptosis by neutralizing free oxygen species using agents like vitamin C and vitamin E; ferritin, glutathione, and a number of enzymes; as mentioned before, administration of vitamin C could suppress the apoptotic effects of benzodiazepines through "restoration of cellular glutathione reservoirs" (4, 118, 126-129). …”
Section: Discussionmentioning
confidence: 99%